Biological characterization of the sex pheromone compounds Tecia solanivora Povolny (Lepidoptera: Gelechiidae) - BOSA-O., CARLOS FELIPE; WITZGALL, PETER; BENGTSSON, MARIE; COTES-P., ALBA M. (Revista Colombiana de Entomología, 2005)
The different constituent compounds of the sex pheromone of Tecia solanivora were identified and characterized chemically and biologically. Identification was done with a mass spectrometer, chemical and biological characterization of the pheromone with gas chromatography and electroantennographic detection techniques, and evaluation of the different proportions and blends of the compounds through biological assays under wind tunnel conditions. In order to select the most promising pheromone blend for the efficient capture of T. solanivora males in the field, active pheromone compounds were evaluated in three rural areas corresponding to Mosquera (Cundinamarca), Siachoque and Toca (Boyacá). The highest male captures were obtained with the combination of the compounds E3-12Ac and 12Ac in the proportion (10:2), respectively, with 32 males per trap. However when the main compound was tested alone, which constitutes the commercial pheromone, only 16 males per trap were caught.